Changing agricultural landscapes in Ethiopia: examining application of adaptive management approach - Haileslassie, Amare; Mekuria, Wolde; Schmitter, Petra S.; Uhlenbrook, Stefan; Ludi, Eva (MDPI, 2020)
Ethiopia has decades of experience in implementing land and water management interventions. The overarching objectives of this review were to synthesize evidences on the impact of implementation of land and water management practices on agricultural landscapes in Ethiopia and to evaluate the use of adaptive management (AM) approaches as a tool to manage uncertainties. We explored how elements of the structures and functions of landscapes have been transformed, and how the components of AM, such as structured decision-making and learning processes, have been applied. Despite numerous environmental and economic benefits of land and water management interventions in Ethiopia, this review revealed gaps in AM approaches. These include: (i) inadequate evidence-based contextualization of interventions, (ii) lack of monitoring of bio-physical and socioeconomic processes and changes post implementation, (iii) lack of trade-off analyses, and (iv) inadequacy of local community engagement and provision of feedback. Given the many uncertainties we must deal with, future investment in AM approaches tailored to the needs and context would help to achieve the goals of sustainable agricultural landscape transformation. The success depends, among other things, on the ability to learn from the knowledge generated and apply the learning as implementation evolves.